Implementation of the Policy on Certification of Land Ownership Transfer through Sale and Purchase at the National Land Agency, Barru Regency - Andi Rachmat; Ulmi Sri Mutia (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal